A comparative study on the gel transition, structural changes, and emulsifying properties of anhydride-esterified agar with varied degrees of substitution and carbon chain lengths. (August 2023) - Zhang, Luyao; Xiao, Qiong; Zhang, Yonghui; Weng, Huifen; Wang, Siyuan; Chen, Fuquan; Xiao, Anfeng
Abstract: In this study, agar was chemically modified with C12–C18 anhydrides. The effects of anhydrides with different degrees of substitution (DSs) and carbon chain lengths on the physicochemical and emulsifying properties of agar were investigated. The gel properties of the esterified agar decreased as the DS and carbon chain length increased. The addition of long hydrophobic chains and carboxyl groups led to good surface activity (surface tension of 29.1 mN/m, interfacial tension of 6.6 mN/m, and contact angle of 108.67°) and high negative charge (−20.23 mV) of the esterified agar. Fourier transform infrared spectral results showed that as the DS and carbon chain length increased, the carboxyl groups and long hydrophobic chains of anhydrides affected the intermolecular and intramolecular hydrogen bonds of agar. Scanning electron microscopy showed that the esterified agar had larger pores and looser network structure than native agar. Thermal stability showed that the esterified agar had strong electrostatic repulsion and chain flexibility, thereby reducing thermal stability. Appropriate hydrophobicity and electrostatic interaction of the long-chain anhydride-esterified agar resulted in the small particle size (60.533 μm), high emulsifying stability, and other properties of the prepared emulsion. In addition, increasing the DS and carbon chain length enhanced the emulsifying properties. The structural and amphiphilic properties of agars esterified by anhydrides with different chain lengths were investigated to stabilize the ability of agar-based emulsions. Graphical abstract: Image 1 Highlights: Long-chain anhydride linked agar shows gel properties and surface activity transition. Break of H-bonds in agar molecules results gel presents loose network structure. Increased hydrophobic long carbon chain facilitates formation of agar-based emulsions. Electrostatic repulsion produced by carboxyl groups makes stable agar emulsions.